Optymalizacja Układu Drgającego przy Okresowym Wymuszeniu Impulsowym - Cempel, C. (Engineering Transactions, 1971)
The solution is given to the problem of finding the minimum residual vibrations and the transmission of forces into the foundation of a system loaded by periodical impulsive forces. Under the assumption of equal pulse are the optimum pulse-shape and frequency have been determined.